2008
DOI: 10.1107/s1600536808035034
|View full text |Cite
|
Sign up to set email alerts
|

(E)-4-[(1,5-Dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-yl)iminomethyl]phenyl 4-bromobenzenesulfonate

Abstract: In the title compound, C24H20BrN3O4S, the central benzene ring makes dihedral angles of 17.13 (13), 39.83 (13) and 58.37 (13)°, respectively, with the pyrazolone ring, the bromo­benzene ring and the terminal phenyl ring. In the crystal structure, the packing is stabilized by a weak non-classical inter­molecular C—H⋯O hydrogen bond which links the mol­ecules into a chain propagating in [100].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Otherwise, the molecule is bent at the sulfonate group with the C1-S1-O3-C8 torsion angle of 50.7 (3). The other bond parameters are similar to those observed in 4-Methyl-2-oxo-2,3-dihydro-1-benzopyran-7-yl benzenesulfonate (Yang et al, 2008) (Han et al, 2008) and 2-Methyl-3-nitrobenzyl cyanide (Chen et al, 2009).…”
Section: Data Collectionsupporting
confidence: 75%
See 1 more Smart Citation
“…Otherwise, the molecule is bent at the sulfonate group with the C1-S1-O3-C8 torsion angle of 50.7 (3). The other bond parameters are similar to those observed in 4-Methyl-2-oxo-2,3-dihydro-1-benzopyran-7-yl benzenesulfonate (Yang et al, 2008) (Han et al, 2008) and 2-Methyl-3-nitrobenzyl cyanide (Chen et al, 2009).…”
Section: Data Collectionsupporting
confidence: 75%
“…For the herbicidal activity of hydroquinone derivatives, see: Bao et al (2007); Liu (2002). For related structures, see: Chen & Zhang (2009); Han et al (2008); Yang et al (2008). For hydrogen-bond motifs, see: Bernstein et al (1995); Etter (1990).…”
Section: Related Literaturementioning
confidence: 99%
“…There has been steady growth of interest in the synthesis, structure, and reactivity of Schiff bases due to their potentially biological activities such as protein and enzyme mimics (Santos et al, 2001). Among the large number of compounds, 4amino-1,5-dimethyl-2-phenylpyrazol-3-one forms a variety of Schiff bases with aldehydes, and the synthesis and crystal structures of some of them, such as (E)-5-[(1,5-dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-ylimino)methyl]-2methoxyphenyl 4-bromobenzenesulfonate (Guo et al, 2010) and (E)-4-[(1,5-dimethyl-3-oxo-2-phenyl-2,3-dihydro-1Hpyrazol-4-ylimino)methyl]phenyl 4-bromobenzenesulfonate (Han et al, 2008) have been reported.…”
Section: S1 Commentmentioning
confidence: 99%
“…For general background to the use of Schiff base derivatives in the development of protein and enzyme mimics, see: Santos et al (2001). For related structures, see: Zhang et al (2006); Han et al (2008); Guo et al (2010). For reference bond-length data, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%
“…Schiff bases have extensively been studied because of their potentially biological activities such as protein and enzyme mimics (Santos et al, 2001). Among the large number of compounds, 4-amino-1,5-dimethyl-2-phenylpyrazol-3-one forms a variety of Schiff bases with aldehydes, and the synthesis and crystal structures of some of them, such as (E)-5-((1,5-Dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-ylimino)methyl) -2-methoxyphenyl 4-bromobenzenesulfonate (Guo et al, 2010), (E)-4-((1,5-Dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-ylimino)methyl) phenyl 4bromobenzenesulfonate (Han et al, 2008) and (E)-4-(2-(4-Chlorobenzyloxy)benzylideneamino) -2,3-dimethyl-1phenyl-1,2-dihydropyrazol-5-one (Zhang et al, 2006) have been reported. Herewith we report the synthesis and crystal structure of the title Schiff base compound.…”
Section: S1 Commentmentioning
confidence: 99%